Current Knowledge Regarding the Interaction Between Oral Bone Metabolic Disorders and Diabetes Mellitus - Wang, Xiaofeng; Wang, Huiyu; Zhang, Tianfu; Cai, Lu; Kong, Chenfei; He, Jinting (Frontiers in Endocrinology, 2020)
Diabetes mellitus, as one of the main chronic diseases affecting human health, has shown an increasing prevalence in recent years. Diabetes mellitus can cause bone metabolic disorders in patients, leading to osteoporosis, a higher risk of traumatic fracture, and other bone diseases. Bone metabolic disorders in the oral cavity principally manifest as periodontitis, loss of alveolar bone, and failure of implant osseointegration. In recent years, numerous studies have shown that there is a complex interaction between bone metabolic disorders and diabetes mellitus. This paper reviews the adverse effects of diabetes on the oral bone metabolism disorders such as alveolar osteoporosis and bone loss in patients with periodontitis, discusses the potential mechanism of diabetes increasing bone loss, and suggests the prevention and treatment of oral bone loss in patients with diabetes mellitus.